ENVIRONMENTAL AND HEALTH IMPACTS OF PLASTIC BAGS: AWARENESS AND MANAGEMENT PRACTICES IN KADUNA METROPOLIS, NIGERIA - Yunusa, Iliyasu Garba; Dalhatu, Bello; Shehu, Aliyu Abubakar; Suleiman, Kabir; Sanni, Tajuddeen; Namakka, Murtala (FUDMA JOURNAL OF SCIENCES, 2025)
The surge in plastic usage has led to an increase in plastic waste, creating complex environmental, health, and socio-economic challenges, including in developing nations. This study focuses on Kaduna Metropolis, North Western Nigeria, to assess the awareness and management practices surrounding plastic bag waste. It examines the demographic and socio-economic factors influencing these practices while highlighting the prevalence of unsustainable methods such as open dumping and burning, which exacerbate environmental degradation and health risks.Findings reveal that Gender, a ge, marital status, and education significantly impact waste management behaviors. Women, despite limited roles in decision-making, are central to domestic waste disposal, while younger and middle-aged adults dominate waste-related activities. The study also underscores the high prevalence of food and plastic waste, pointing to the urgent need for targeted strategies to promote sustainable practices.Recommendations emphasize public education campaigns tailored to community demographics, the development of adequate waste management infrastructure, policy enforcement to discourage harmful practices, and community based initiatives involving professionals and students. Collaboration with educational institutions to integrate waste management into curricula is identified as a critical long-term strategy. The research offers actionable insights for addressing the pressing issues of plastic pollution and fostering sustainable waste management behaviors in urban settings.